Efficacy of an experimental toothpaste containing sodium bicarbonate, sodium hyaluronate and sodium fluoride on gingivitis - Alyson Axe; Nisha Patel; Jimmy Qaqish; Martin R. Ling; Mako Araga; Charlie Parkinson; Chaju Ram Goyal (BMC, 2024)
Abstract Background Gingivitis is driven by plaque accumulation and, if left untreated, can progress to irreversible periodontitis. For many, the mechanical action of toothbrushing does not achieve adequate plaque control. The aim of this study was to investigate whether twice-daily use of a toothpaste containing 0.2% high molecular weight (HMW) sodium hyaluronate with 67% sodium bicarbonate and 0.221% sodium fluoride (experimental toothpaste) could improve gingival health compared with a regular fluoride toothpaste (negative control). The study also assessed whether the experimental toothpaste could provide additive gingival health benefit over a toothpaste containing only 67% sodium bicarbonate and 0.221% sodium fluoride (positive control). Methods This was a single-center, examiner-blinded, randomized, clinical study in healthy adults with mild-to-moderate gingivitis. At baseline, after abstaining from toothbrushing for 12 h, prospective participants underwent oral soft tissue (OST) and oral hard tissue examination followed by assessments for gingival inflammation (Modified Gingival Index [MGI]), gingival bleeding (Bleeding Index [BI]), and supra-gingival plaque (Turesky Plaque Index [TPI]). Eligible participants were stratified by gender and baseline number of bleeding sites (low: <45; high: ≥45 bleeding sites). Following randomization, participants underwent prophylactic dental treatment. Participants received a full OST examination, MGI, BI and TPI assessments after 3 days, 1, 2 and 6 weeks of product use. Results In total, 110 participants were screened for study entry and all were randomized to receive one of three toothpastes (experimental: sodium hyaluronate, sodium bicarbonate, sodium fluoride; positive control: sodium bicarbonate, sodium fluoride; negative control: regular fluoride toothpaste). For all measures, significant improvements were observed in participants receiving either sodium bicarbonate-containing toothpaste (experimental or positive control) compared with the regular fluoride toothpaste (negative control) at week 6. No significant difference was observed in any assessment or visit comparing the experimental toothpaste with the positive control. Conclusions Both the experimental and the positive control toothpastes demonstrated clinically relevant improvements in gingival health compared with a regular fluoride toothpaste (negative control). However, no additional gingival health improvement was observed for the experimental toothpaste compared with the positive control, therefore, no additional gingival health benefit can be attributed to the inclusion of sodium hyaluronate in this formulation. Trial registration ClinicalTrials.gov Identifier: NCT04737538 (04/02/2021).